Language Style Used on the Caption of @ecobites.official Instagram Account: A Stylistic Study - Putri Wulan Septiani; Lina Purwaning Hartanti (Hasanuddin University, 2026)
The language style used in captions is one of the advertising strategies to attract audiences. Captions, as a linguistic aspect, play an important role in supporting the effectiveness of advertising on Instagram. Through using this language style, Ecobites, as an eco-friendly product can create advertisements that can spread awareness about the importance of using eco-friendly products. This aims to persuade the audience to choose ECOBITES. Therefore, examining Instagram captions as advertising tool is worth to studying. Thus, the objective of this study is to identify the types of the language style used in the Instagram captions of the @ecobites.official account. The theory that was used in this study is Keraf’s (2007) theory. This study uses qualitative method, with documentation technique to collect the data. The subjects are 15 captions from the @ecobites.official Instagram account. The results show that @ecobites.official Instagram captions used varied language styles, they are 1) Based on the word choice, @ecobites.offficial Instagram captions were dominated by conversational language style; 2) @ecobites.official Instagram captions were dominated by intermediate language style when viewed based on tone; 3) Based on the sentence structure, Ecobites’ Instagram captions were dominated by climax and repetition language style; and 4) Language style based on the direct and indirect meaning that used in Ecobites’ Instagram captions were dominated by rhetorical language style.